Strength Behaviour Of Biomass Fiber-Reinforced Concrete Slab - Jung, Chai Teck; Loon, Lee Yee; Kwong, Tang Hing; Boon, Koh Heng (International Journal of Sustainable Construction Engineering and Technology, 2012)
This paper investigates the compressive strength and flexural strength of biomass fibre-reinforced concrete slab. The main objective of this study is to examine the effect of biomass aggregate and fibre glass on the concrete slab strength. The biomass aggregate is used to replace the natural aggregates. A total of 36 slab samples (250 mm x 600 mm x 50mm thick) and 36 numbers of 150 mm cube samples containing 0%, 30%, 60% and 100% biomass aggregate were prepared. The E-class fibre and Supracoat SP800 were added to increase the strength and to achieve the required workability. All the samples were cured in water with room temperature of around 27oC and tested at the age of 7, 14 and 28 days respectively. The result showed that cube specimens containing 30% biomass aggregate concrete achieved minimum strength of 15 MPa at 28 days. The flexural strength for slab specimens containing 30% biomass aggregate, Supracoat SP 800 and fibre glass gained higher strength compared with control specimens. The 100% biomass aggregate slab achieved 88% of the control specimen strength. The workability was between 150 mm to 170mm slump. The density of the specimens was reduced 20% for cube and 28% for slab compared with control specimens. It can be concluded that the biomass aggregate has good potential as partial aggregate replacement in slab construction when combined with the use of glass fibre and superplasticizer. However, more research needs to be carried out to self-compacting biomass aggregate concrete for sustainable construction